Social Class-Based Discrimination and Psychological Symptoms Among Socioeconomically Disadvantaged College Students: The Moderated Mediation Role of Stress Mindset and Rumination - Wu, Jia; Li, Qianfeng; Wu, Qinglu; Li, Qiaoling (Frontiers in Psychiatry, 2022)
Discrimination as a crucial stressor damages the mental health of socioeconomically disadvantaged persons through increased ruminative thinking. A “stress-is-enhancing” mindset may protect the mental health of socioeconomically disadvantaged persons under the pressures of perceived discrimination and rumination. This study examined the mediating role of rumination and the moderating role of stress mindset in the relationship between perceived discrimination and psychological symptoms among socioeconomically disadvantaged college students. A total of 919 socioeconomically disadvantaged undergraduates (48.4% female, ages 17–25) were recruited. The results indicated that perceived discrimination was positively associated with psychological symptoms among socioeconomically disadvantaged undergraduates through rumination (B = 0.11, boot SE = 0.01, boot 95% CIs = [0.08, 0.13]). Importantly, stress mindset moderated the indirect association between perceived discrimination and psychological distress through rumination (B = -0.18, boot SE = 0.08, boot 95% CIs = [-0.32, -0.03]). Specifically, compared to persons with low levels of the stress-is-enhancing mindset, the indirect effect of perceived discrimination on psychological distress through rumination was weaker among individuals with high levels of the stress-is-enhancing mindset. The findings provide support for future intervention practice to promote a stress-is-enhancing mindset to protect the mental health of socioeconomically disadvantaged college students under the pressures of perceived discrimination and rumination.